Indications and Results of Coronarography in Senegalese Diabetic Patients: About 45 Cases - SCT, Ndao; ND, Gaye; M, Dioum; AA, Ngaide; JS, Mingou; MB, Ndiaye; M, Diao; SA, Ba (Journal of Cardiology and Cardiovascular Medicine, 2017)
Introduction: Coronary disease accounts for 75% of diabetic mortality. Coronary angiography reveals lesions that are often diffuse, staggered and multi-truncated. The objective of this study was to determine the indications and results of coronary angiography in diabetic patients. Method: This is a cross-sectional, descriptive and analytical study which took place from May 2013 to July 2015 at the cardiology clinic of the Aristide Le Dantec hospital. We have included all diabetics who have benefited from coronary angiography by studying clinical and paraclinical data, particularly coronary angiography ones. Results: During this period, 400 patients had coronary angiography, including 45 diabetics, a hospital prevalence of 11.25%. The average age of our patients was 62.27 y/o with extremes of 44 and 85 y/o. The sex ratio was 1.6 in favor of men. Diabete was revealed in 42 patients. Almost all patients were type II diabetics (44 patients) since 9.94 years in average. The associated cardiovascular risk factors were hypertension 66.7% and dyslipidemia 49.6%. Only 4 patients had typical chest pain. The electrocardiogram was abnormal in 84.4% of cases with 26 cases of SCA ST +. Coronary angiography was abnormal in 37 patients with significant stenosis in 30 patients. A single-truncular lesion was found in 14 cases, 8 had bi-truncular and other 8 had tri-truncular one. The anterior interventricular artery and the segment II of the right coronary were the most affected branches. Concerning the management, 14 patients had angioplasty with an active stent, 8 patients had medical treatment alone and 9 patients had coronary artery bypass surgery. Accidents occured for 4 patients, two of whom had arterial spasm, one of a vagal discomfort and another had an occlusion of the circumflex that led to the implantation of a stent. Conclusion: Diabetes is accompanied by progressive coronary atherosclerosis, which has an adverse effect on patients' prognosis. Tri-truncal affection and indications for coronary artery bypass surgery are common